Life - On rice - Baker, Donald L. (New York Carlton Press, 1963)
Autobiographical narration of a U.S. Army man's capture on Corregidor, Life in prison camps in the Philippines and Japan.
Keywords: World War, 1939-1945 -- Personal narratives, American; World War, 1939-1945 -- Campaigns -- Philippines; World War, 1939-1945 -- Prisoners and prisons